Four-stranded nucleic acids: structure, function and targeting of G-quadruplexes - Huppert, Julian Leon (Chemical Society reviews, 2008)
There are many structures that can be adopted by nucleic acids other than the famous Watson-Crick duplex form. This tutorial review describes the guanine rich G-quadruplex structure, highlighting the chemical interactions governing its formation, and the topological variants that exist. The methods that are used to study G-quadruplex structures are described, with examples of the information that may be derived from these different methods. Next, the proposed biological functions of G-quadruplexes are discussed, highlighting especially their presence in telomeric regions and gene promoters. G-quadruplex structures are the subject of considerable interest for the development of small-molecule ligands, and are also the targets of a wide variety of natural proteins.